Sistem Notifikasi Monitoring Kualitas Udara Dalam Ruangan Produksi Berbasis Internet Of Things (Iot) Menggunakan Esp8266 - Fuad Hasyim; Imam Suharjo (UNIVERSITAS STEKOM, 2024)
This research develops an indoor air quality monitoring notification system for production rooms based on the Internet of Things (IoT) using the ESP8266. The system is designed to detect and provide early warnings of air pollution in production rooms. The Sharp GP2Y1010AU0F sensor is used to measure the concentration of dust particles in the air. Data from the sensor is sent to the ESP8266 module connected to the internet. This information is then forwarded to the Blynk application, enabling real-time monitoring through mobile devices. If the dust concentration exceeds the predetermined threshold, the system will activate the buzzer as an alarm. Test results show that this system can provide accurate and responsive notifications, thus helping to improve safety and health in the production environment.